(untitled) (Altre Modernità, 2010)
The present article tries to explain the narrative functions of the rituals of death and conmemorative acts in Réquiem por un campesino español. In that text we find the conflict of the spanish civil war taking the scene of a requiem mise, where the time of the main character´s narration in the first person recovers in an anleptical way the past memory before the antagonist character´s death whom that requiem mise is given to. In the scene, although, four points of fuge are taking in order to break the superficial monological discourse of the main character, a priest, and make the testimonial relation, not a ritual of death, but a rit of mea culpa. As a testimonial relation, moreover, this text allows us to discuss the function of the death as a moral exemplum and as a defense of the statu quo, as far as the use of externalization that, since Antígona, the died subject figure determines in the social relationships.